An Adaptive Regulator for Space Teleoperation System in Task Space - Chao Ge; Weiwei Zhang; Hong Wang; Xiaoyi Li (Abstract and Applied Analysis)
The problem of the gravity information which can not be obtained in advance for bilateral teleoperation is studied. In outer space exploration, the gravity term changes with the position changing of the slave manipulator. So it is necessary to design an adaptive regulator controller to compensate for the unknown gravity signal. Moreover, to get a more accurate position tracking performance, the controller is designed in the task space instead of the joint space. Additionally, the time delay considered in this paper is not only time varying but also unsymmetrical. Finally, simulations are presented to show the effectiveness of the proposed approach.